Physical Education From The Perspective Of Islamic Education Philosophy - Umar*, Asril; Salminawati, Salminawati; Usiono, Usiono (Riwayat: Educational Journal of History and Humanities, 2023)
This paper aims to explain that physical education is often associated with physical health and sports skills. However, in the context of Islamic education philosophy, physical education has a deeper dimension. This article explains the position and importance of physical education in the perspective of Islamic education philosophy. Islamic education emphasizes the balance between the physical, spiritual, intellectual and emotional aspects of individual development. Physical education is not only considered as a physical activity, but also as a means to get closer to Allah, appreciate the blessings given by Him, and as a form of gratitude for the existence of a healthy and strong body. In addition, physical education is also a form of practicing discipline, patience, and cooperation in accordance with the values taught in Islam. Through this approach, physical education can be an integral part of a comprehensive Islamic education system, which aims to develop a balanced individual in both physical, spiritual and social aspects.